Formulasi Kumulasi Gugatan Yang Dibenarkan Tata Tertib Acara Indonesia - Kidung Sadewa; Heri Hartanto, S.H., M.H (Verstek, 2017)
The aim of this research is to understanding the cumulative claim based on Indonesian civil procedural law by analyzing two verdict of supreme court since no civil procedural rule that prohibit cumulative claim.     This is prescriptive doctrinal or normative research with the case approach, this research use the primary law sources and secondary law sources as legal source. The technique of collecting legal material in this research use library research and use inductive method as the technique of analyzing legal material.    The unpresent of rule in Indonesian civil procedural law that prohibit cumulative claim inevitablely permit cumulation claim.  However in practice, there is a contradiction of two supreme court’s verdicts which are verdict number 2157 K/Pdt/2012 that permit cumulative claim and verdict number 571 PK/PDT/2008 that prohibit cumulative claim. According to two analyzed verdicts, it can be acquired that permitted cumulative claim formulation in Indonesian civil procedural law required close connection, legal connection and consistency at the claim.     Keywords: Onrechtmatige Daad, Tort, Cumulative Claim